A NEW ULTRASONIC CRITERION OF EVALUATING SPLEEN DIMENSIONS IN CHILDREN AND DETERMINATION OF THE RANGE OF NORMAL ORGAN’S DIMENSIONS - O. V. Vozgoment; M. I. Pykov; N. V. Zaytseva; A. A. Akatova; Y. A. Ivashova; V. M. Chigvintsev (Педиатрическая фармакология, 2014)
The study was aimed at establishing a new ultrasonic criterion of evaluating spleen dimensions in children (area of the maximum axial section) and determining the range of normal spleen dimensions. Patients and methods: We analyzed 838 ultrasonic spleen examinations in 3‑15‑year-old children and determined the area of the maximum axial section by tracing the scan obtained with a medical device. Results: on the basis of ultrasonic examination data analysis, we established a formula, which helps to calculate the spleen section area with the organ’s length and thickness. We performed retrospective analysis of 4,001 standard ultrasonic examinations followed by formula evaluation of the area of maximum axial section. Conclusion: on the basis of the comparative analysis of the measured and calculated areas of the maximum spleen axial section, we established a range of normal values of this parameter taking age and sex into account.